El derrame de petróleo en la refinería La Pampilla en enero de 2022 y su afectación social en el distrito de Ancón - Yupanqui-Reyes, Araceli (2024)
The objective of this study is to recognize the socioeconomic and health impacts on the social actors in the district most affected by the oil spill. Using the "Qualitative Point" methodology, the district of Ancon was selected as the study area due to the significant impact of the spill. Additionally, a literature review was carried out to contextualize and determine the scope of the socioeconomic and health impacts of the spill, and to identify the most affected actors through the social actor mapping methodology, which identified four key actors. Furthermore, through in-depth interviews and field data collection, severe socioeconomic impacts were revealed, with total economic losses ranging between 80% and 100%. Finally, the health damage caused by the spill was identified.